Mesoporous Silica Materials as Drug Delivery: "The Nightmare" of Bacterial Infection - Gounko, Iouri (My University, 2018)
Mesoporous silica materials (MSM) have a great surface area and a high pore volume, meaning that they consequently have a large loading capacity, and have been demonstrated to be unique candidates for the treatment of different pathologies, including bacterial infection. In this text, we review the multiple ways of action in which MSM can be used to fight bacterial infection, including early detection, drug release, targeting bacteria or biofilm, antifouling surfaces, and adjuvant capacity. This review focus mainly on those that act as a drug delivery system, and therefore that have an essential characteristic, which is their great loading capacity. Since MSM have advantages in all stages of combatting bacterial infection; its prevention, detection and finally in its treatment, we can venture to talk about them as the “nightmare of bacteria”.
Keywords: Mesoporous silica; Multifunctional nanoparticles; Drug delivery; Bacterial infection; Bacterial biofilm; Biofilm; Antibioticresistance; Targeting bacteria; Targeting biofilm